Are we offering palliative care and employing shared decision making in the neonatal intensive care unit? A 10-year retrospective chart review - Sawyer Karabelas-Pittman; Helen Coo; Hannah Lee; Christine C. Moon; Gillian MacLean (PEC Innovation)
Objective: Perinatal palliative care (PPC) supports families with a fetal diagnosis of a life-limiting condition or who are facing preterm labour at the limits of viability. Shared decision making (SDM) is the gold standard approach in PPC. The objectives of this study were to describe the Neonatal Intensive Care Unit (NICU) team's involvement in PPC and the extent of SDM at an academic hospital in southeastern Ontario, and the frequency with which PPC was offered, accepted and received for live births. Methods: We retrospectively reviewed charts for births from January 2010–January 2020 where a life-limiting condition (LLC) had been prenatally diagnosed or there was threatened preterm labour (TPTL) at the limits of viability. Frequency distributions were used to summarize the NICU team's involvement, extent of SDM, and data related to PPC provision. Results: The LLC group included 73 patients. The NICU team was consulted for 26 (36 %). Among the 10 consults that involved decision making, SDM was documented in 9 instances (90 %). PPC was offered to 9 of 60 LLC families (15 %) with a live birth and was accepted by 8 (89 %). The TPTL Group included 112 patients. Seventy (62 %) received a consult with the NICU team. SDM was documented in 34 of 39 consults (87 %) that involved decision making. PPC was offered to 28 of 90 families (31 %) who experienced a live birth and was accepted by 16 (57 %). Conclusion: Our results demonstrate the need for standardized consultation and palliative care referral protocols to advance access to and quality of neonatal end-of-life care.